Secondary Hyperparathyroidism and Depression in Renal Failure - Cengiz, K.; Özkan, A.; Kesim, G.; Özdemir, G.; Deniz, O. (My University, 1998)
Depression is the most commonly described psychological disorder seen in chronic renal failure (CRF) patinets. Apart from different psychological theories about the pathogenesis of depression in CRF, the literature also refers to organic factors, because CRF is accompanied by various pathobiocemical changes. Parathyroid hormon is one of the most important uremic toxin in CRF. But there are few and conflicting results about the secondary hyperparathyroidism (SHP) and depression in CRF. This study was aimed at studing the relation between SHPT and depression in CRF. In this study 31 CRF patients (18 male and 13 female) were studied. The 'Hamilton Depression Scale' and the Mini Mental Test were performed. On the same day serum values of BUN, Creatinine, electrolytes and PTH were measured. Serum PTH levels were higher in the patients with depressive CRF than non-depressive CRF (p < 0.001). But there was no relationship between depression and BUN, creatinine, electrolyte levels, sex and duration of the disease (p > 0.005). As a result of our findings it has been concluded that high levels of PTH can play an important role in the pathogenesis of depression in CRF. We purpose keeping SHPT under control rather than giving nonspecific antidepressants in the treatment of this type of depression. Further controlled studies are indicated to enlighten the psychopathology of depression seen in CRF.
Kronik Böbrek Yetmezliğinde Sekonder Hiperparatiroidi ve Depresyon
Keywords: Depression; Renal Failure; Secondary Hyperparathyroidism